An introduction to language - Fromkin, Victoria; Rodman, Robert
Assuming no prior knowledge of linguistics, AN INTRODUCTION TO LANGUAGE, Tenth Edition, is appropriate for a variety of fields--including education, languages, psychology, cognitive science, anthropology, English, and teaching English as a Second Language (TESL)--at both the undergraduate and graduate levels. This completely updated edition retains the clear descriptions, humor, and seamless pedagogy that have made the book a perennial best-seller, while adding new information and exercises that render each topic fresh, engaging, and current